Implementation of Free Legal Aid (Pro Bono) for the Poor in Indonesia (Universitas Negeri Semarang, 2022)
The obligation to provide free legal aid by advocates has been stipulated in Article 22 of Law Number 18 Year 2003 regarding Advocate. As a respectful profession (officium nobile), advocate has duty and responsibility to embody rule of law principle. Pro bono legal service is a duty of every advocate as mandated by Advocate Law. This research uses normative approach and is descriptive analysis in manner. The researchers uses library research to process the data. This research aims to analyse the implementation of pro bono legal service by advocates and bar association in Indonesia. Despite of bar association, in this regard Perhimpunan Advokat Indonesia (PERADI) has established a special work unit to implement the function of pro bono legal service, Pusat Bantuan Hukum in the regions in Indonesia, However, in practice, the interest of lawyers to carry out this obligation and their reporting is still minimal. This study intends to determine the cause of the lack of interest in lawyers in provide free legal assistance.